Faktor Risiko Ketuban Pecah Dini - Stefani Melisa (Yayasan Pendidikan Medika Indonesia, 2021)
Premature Rupture of Membranes (PROM) . When rupture occurs before delivery and before 37 weeks of gestation, it is also called preterm PROM. PROM is one of the causes of morbidity and mortality in obstetrics. The cause of PROM has not been determined with certainty. The interaction of PROM risk factors is the determinant of this incident. The purpose of this paper is to determine the risk factors for premature rupture of membranes. The method used is literature review by searching for premature rupture of membranes, determinants, and obstetrics on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From a review of the existing literature, risk factors for PROM include maternal age during pregnancy, history of parity, maternal education level, and history of infection in the mother.